Predictors of quality of life and attitude to ageing in older adults with and without dementia. (4th March 2021) - Kisvetrová, Helena; Herzig, Roman; Bretšnajdrová, Milena; Tomanová, Jitka; Langová, Kateřina; Školoudík, David
Abstract: Objectives: This study explored the quality of life (QoL) and attitudes to aging in older adults with and without dementia, and ascertained the main factors that predict QoL and attitude to ageing. Methods: A cross-sectional study involving 563 community-dwelling adults with (PwD) and without dementia (PwoD) >60 years of age was conducted in three Czech regions. A tools battery including the Quality of Life-Alzheimer's Disease Scale, Geriatric Depression Scale, Patient Dignity Inventory, Attitude to Aging Questionnaire (AAQ), Short Physical Performance Battery, and Barthel Index, were administered. Results: PwD had worse scores in QoL and AAQ (both p = 0.0001). Less depression ( p < 0.001), better sense of dignity ( p < 0.05), and lower pain ( p < 0.05) in PwoD predicted better scoring for QoL and AAQ. Physical ability in PwoD ( p < 0.05), living alone ( p < 0.05) and self-sufficiency ( p < 0.001) in PwDwere predictors influencing QoL.Age ( p < 0.01) in PwoD, gender ( p < 0.05) and physical ability ( p < 0.001) in PwD influenced AAQ. Conclusions: This research is the first study to show that dignity can influence the QoL and attitude to aging in community-dwelling older adults. Our findings suggest that depression and dignity are common predictors of QoL and AAQ in older adults with and without dementia.